MUSIC, MODULARITY AND SYNTAX - Valenzuela, Javier; Hilferty, Joseph (International Journal of English Studies, 2009)
First generation cognitive science has always maintained that the mind/brain is a modular system. This has been especially apparent in linguistics, where the modularity thesis goes largely unquestioned by the linguistic mainstream. Cognitive linguists have long disputed the reality of modular architectures of grammar. Instead of conceiving syntax as a computational system of a relatively small set of formal principles and parameters, cognitive linguists take the notion of grammatical construction to be the basic unit of syntax: syntax is simply our repertoire of form-meaning pairings. On such a view, there is no a-priori reason to believe that semantics and phonology cannot affect syntax. In the present paper, we want to take things a step further and suggest, more generally, that language is not a module of cognition in any strict sense. We present preliminary results from research in progress concerning the effect of music on grammatical constructions. More specifically, our experiment compares reaction times between two grammatical constructions that differ in semantics and intonational curves but share lexical material. Our data so far suggests that subjects take less time reading the construction when the semantic bias and intonation match than in non-matching cases. This, we argue, suggests not only that semantics, phonology and syntax form an information bundle (i.e. a construction in the cognitive linguistic sense), but that perceived similarity of music can influence linguistic cognition.